Analisa Difraksi Sinar-X pada Baja Tahan Karat Austentitik dan Feritik (Uji Laboratorium) - Siti Triaminingsih (Faculty of Dentistry, Universitas Indonesia, 2015)
X- rays with wavelength in the range 0,5 to 2,5 Å, have a very short wavelength compare to the visible light wavelength in order of 6000 Å. Therefore, x-rays can be used for determination of the finest structure of materials by using the x-rays diffraction method. A solid crystalline consist of atoms were orderly arrangement and when a beam of x-rays strikes at that crystalline, the atom act as a center of diffraction. Since x-rays are electromagnetic waves with the wavelength penetrated into the distance between planes of atoms, the x-ray diffraction can be seen regarding using the Bragg'slaw (χ = 2d sin θ). Austensitic stainless steel could be transformed from γ phase (FCC) to α phase (BCC) by shear induced mechanism. It was proved that the austensitic stainless steel have a metastable properties in room temperature and can be changed by plastic deformation. The ferritic stainless steel have more stable, and it was different from austensitic stainless steel. The crystal structure of ferritic stainless steel will not change by plastic deformation. The transformation on austensitic stainless steel can be determined by x-rays diffraction method. The diffraction pattern produced have peaks of γ phase (FCC) and α phase (BCC). However, the ferritic stainless steel only produced diffraction peaks of α phase (BCC). Therefore the different of austensitic stainless steel and ferritic stainless steel could be seen in the diffraction pattern. The purpose of this study is to determine the x-rays diffraction pattern of austensitic and ferritic stainless steel by powder method.